The Correlation of Landslide Disaster with Increased Cases of Atopic Dermatitis in Disaster Victims: Review - Carissa Aulia Ramadhani Sutopo (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Landslides not only bring physical damage, but also trigger various health problems, including an increase in cases of atopic dermatitis. The post-landslide environment conditions that are humid, dusty, and limited access to clean water in evacuation centers worsen the skin health of the survivors. Exposure to allergens from soil, mold, and disaster stress further increases the risk of skin inflammation. Purpose: to analyze the relationship between landslide disasters and the increase in atopic dermatitis cases through environmental factors and explore the effect of limited sanitation and allergen exposure on the increase in atopic dermatitis cases after landslide disasters. Method: this study is a literature review using data from Science Direct, Elsevier, Pubmed, and other databases, analyzing 10 national journals, 20 international journals, and 5 theses. Result: studies show landslides can increase atopic dermatitis cases due to dust, mold, poor sanitation, and stress in evacuation camps. Microbiota changes and immune disruption may worsen symptoms, with microbiota manipulation suggested as therapy. However, impacts vary, especially where emergency sanitation and healthcare are adequate. Conclusion: environmental, sanitation, and microbiota factors influence the severity of atopic dermatitis, especially in landslide-affected areas. Exposure to dust, mold, and limited clean water in evacuation camps can worsen skin conditions, while post-disaster stress weakens the immune system. Health and hygiene education is essential for prevention. However, some studies suggest that the impact of landslides varies depending on the quality of emergency sanitation and healthcare services.